NADPH oxidase-produced superoxide mediated a 50-Hz magnetic field-induced epidermal growth factor receptor clustering. (2nd October 2016) - Feng, Baihuan; Dai, Ahui; Chen, Liangjing; Qiu, Liping; Fu, Yiti; Sun, Wenjun
Abstract: Purpose: A 50-Hz magnetic field (MF) was found to induce epidermal growth factor receptor (EGFR) clustering in our previous study. The aim of this work was to investigate the molecular mechanisms that mediated MF-induced EGFR clustering. Materials and methods: Human amniotic epithelial (FL) cells were exposed to a 50-Hz MF. Total reactive oxygen species (ROS), cytoplasmic and mitochondrial superoxide production were detected by DCFH-DA, DHE and MitoSOX, respectively. EGFR clustering was analyzed using confocal microscopy after indirect immunofluorescence staining. Results: Results showed that exposing FL cells to MF at intensity higher than 0.2 mT for 15 min enhanced total ROS production. Additionally, enhanced total ROS and cytoplasmic superoxide production were observed after exposing cells to MF at 0.4 mT for 5, 15, or 30 min, while mitochondrial superoxide production for 15 or 30 min. Pretreatment with Nox inhibitor, DPI, effectively inhibited MF-induced cytoplasmic superoxide production and subsequent EGFR clustering while mitochondrial superoxide production was not affected. Conclusions: Nox-produced superoxide mediated a 50-Hz magnetic field-induced EGFR clustering.